Farm Workers in Western Canada: Injustices and Activism - Herron, Rachel (Labour / Le Travail, 2017)
This article reviews the book, "Farm Workers in Western Canada: Injustices and Activism," edited by Shirley A. McDonald and Bob Barnetson.